Tuning optoelectronic properties and understanding charge transport in nanocrystal thin films of earth abundant semiconducting materials - Riha, Shannon C., author; Parkinson, Bruce A., advisor; Prieto, Amy L., advisor; Elliott, C. Michael, committee member; Field, Stuart, committee member; Henry, Charles, committee member; Rappe, Anthony, committee member (Colorado State University. Libraries, 2011)
With the capability of producing nearly 600 TW annually, solar power is one renewable energy source with the potential to meet a large fraction of the world's burgeoning energy demand. To make solar technology cost-competitive with carbon-based fuels, cheaper devices need to be realized. Solution-processed solar cells from nanocrystal inks of earth abundant materials satisfy this requirement. Nonetheless, a major hurdle in commercializing such devices is poor charge transport through nanocrystal thin films. The efficiency of charge transport through nanocrystal thin films is strongly dependent on the quality of the nanocrystals, as well as their optoelectronic properties. Therefore, the first part of this dissertation is focused on synthesizing high quality nanocrystals of Cu2ZnSnS4, a promising earth abundant photovoltaic absorber material. The optoelectronic properties of the nanocrystals were tuned by altering the copper to zinc ratio, as well as by introducing selenium to create Cu2ZnSn(S1-xSex)4 solid solutions. Photoelectrochemical characterization was used to test the Cu2ZnSnS4 and Cu2ZnSn(S1-xSex)4 nanocrystal thin films. The results identify minority carrier diffusion and recombination via the redox shuttle as the major loss mechanisms hindering efficient charge transport through the nanocrystal thin films. One way to solve this issue is to sinter the nanocrystals together, creating large grains for efficient charge transport. Although this may be quick and effective, it can lead to the formation of structural defects, among other issues. To this end, using a different copper-based material, namely Cu2Se, and simple surface chemistry treatments, an alternative route to enhance charge transport through nanocrystals thin films is proposed.
Keywords: nanocrystals; photovoltaics; copper selenide; copper zinc tin sulfide; earth abundant materials; photoelectrochemical characterization